How Islamic Thought Provides a Framework for Understanding Religion and the State - H. Muhammad Amri; Andi Aderus; Mirnawati Mirnawati (IQRO: Journal of Islamic Education, 2022)
This qualitative study aims to describe the relationship between the state and religion in the frame of Islamic thought. This qualitative research uses the descriptive-analytical method. All data comes from written materials related to the variables to be discussed and are relevant. In addition, a manual system does a bibliography search. The data were analyzed using the flow model Miles & Huberman. There are three views on the relationship between religion and the state. First, there is the view that Islam is a religion that regulates all aspects of life, including political or state affairs. Second the view that religion has nothing to do with the state and religion and state affairs must be separated. The third is the view that although Islam does not have a constitution, it has a set of ethical values for state life.